The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/lno.11748
|View full text |Cite
|
Sign up to set email alerts
|

Macrofauna as a major driver of bentho‐pelagic exchange in the southern North Sea

Abstract: The contribution of sediments to nutrient cycling of the coastal North Sea is strongly controlled by the intensity of fluxes across the sediment water interface. Pore‐water advection is one major exchange mechanism that is well described by models, as it is determined by physical parameters. In contrast, biotransport (i.e., bioirrigation, bioturbation) as the other major transport mechanism is much more complex. Observational data reflecting biotransport, from the German Bight for example, is scarce. We sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
3
8
0
Order By: Relevance
“…Multi-biotic indices were significantly or highly significantly correlated with pH, organic matter, sediment salinity, and Chl-a content, suggesting that the marine benthic environment is related to pH, and nutrients, which is similar to other studies (Oleszczuk et al, 2021;Toussaint et al, 2021). In the study by Neumann et al (2021), bioturbation and temperature had the highest explanatory power to explain the substantial seasonal variability in observed oxygen and nutrients. The total organic matter content is an important environmental variable for anoxic mineralization (Toussaint et al, 2021).…”
Section: Effects Of Environmental Factors On Macrofaunasupporting
confidence: 86%
See 1 more Smart Citation
“…Multi-biotic indices were significantly or highly significantly correlated with pH, organic matter, sediment salinity, and Chl-a content, suggesting that the marine benthic environment is related to pH, and nutrients, which is similar to other studies (Oleszczuk et al, 2021;Toussaint et al, 2021). In the study by Neumann et al (2021), bioturbation and temperature had the highest explanatory power to explain the substantial seasonal variability in observed oxygen and nutrients. The total organic matter content is an important environmental variable for anoxic mineralization (Toussaint et al, 2021).…”
Section: Effects Of Environmental Factors On Macrofaunasupporting
confidence: 86%
“…The effect of temperature on macrofaunal diversity was also significant in this study, with winter macrofaunal diversity being significantly lower than in other seasons. A number of investigations have concluded that macrofaunal abundance has a highly significant positive correlation with bottom temperature (Shojaei et al, 2015;Neumann et al, 2021), especially in semienclosed bays, which may be related to the drastic changes in bottom temperature (Yang et al, 2021). Multi-biotic indices were significantly or highly significantly correlated with pH, organic matter, sediment salinity, and Chl-a content, suggesting that the marine benthic environment is related to pH, and nutrients, which is similar to other studies (Oleszczuk et al, 2021;Toussaint et al, 2021).…”
Section: Effects Of Environmental Factors On Macrofaunamentioning
confidence: 99%
“…Further elucidation of the tracer experiments is provided in Supporting Information S1. Full details of the incubation method and results are presented byNeumann et al (2021).…”
mentioning
confidence: 99%
“…Aerobic remineraliza-B. Van Dam et al: Benthic alkalinity fluxes from coastal sediments of the Baltic and North seas tion is a key DIC source in physically or biologically ventilated surface sediments (Neumann et al, 2021;Rassmann et al, 2020), followed by microbial sulfate reduction (MSR; Al-Raei et al, 2009). These DIC sources may be further enhanced to varying extents by anaerobic processes like denitrification, as well as iron and manganese reduction, which, like MSR, also produce TA and DIC (e.g., Zeebe and Wolf-Galdrow, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For example, large tidal forcing combined with coarsegrained sediments in the southern North Sea could promote advective over diffusive fluxes and increase the oxygen penetration depth (Billerbeck et al, 2006;Al-Raei et al, 2009). Bioturbation and bioirrigation are also especially important in the coastal North Sea and can explain how sediment-water fluxes of oxygen and other elements vary across season and sediment type (Lipka et al, 2018;Gogina et al, 2018;Neumann et al, 2021;Bratek et al, 2020). In contrast, limited tidal forcing combined with finer-grained sediments in the western Baltic Sea could promote stronger biogeochemical zonation and a greater importance of anaerobic over aerobic processes (Böttcher et al, 2000).…”
Section: Introductionmentioning
confidence: 99%